Bolivia : Fifth Review under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criteria, Rephasing, Augmentation and Extension of the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Bolivia's Fifth Review Under the Stand-By Arrangement (SBA), Request for Waiver of Nonobservance of Performance Criteria (PC), and Rephasing, Augmentation, and Extension of the SBA. The 2004 program was on track. All quantitative PCs were met, with the exception of the end-September PC on central bank credit to the nonfinancial public sector. Macroeconomic developments have been positive, largely reflecting the favorable global environment, although the economy is still vulnerable. Real GDP growth is estimated to have reached 3 3/4 percent in 2004, and is projected to reach 4.5 percent in 2005.